Validation of Rapid and Simple HPLC-UV Method for Diflunisal Determination in Bulk Drug and Human Plasma - Smerikarova, Miglena; Bozhanov, Stanislav; Maslarska, Vania (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Transthyretin amyloidosis is a rare disease currently under wide investigation and many different therapeutic agents were developed for its control and treatment. In addition to the newly discovered drugs, it was also observed drug repurposing of some well-studied therapeutic agents. Diflunisal was developed in 1971 as an anti-inflammatory and analgesic drug but showed good results when used as a kinetic stabilizer of the transthyretin protein. Objectives: Present study describes a high–performance liquid chromatography method for its determination in bulk drug and human plasma by UV detection. Materials and Methods: Isocratic elution of the mobile phase (consisting of 0.1% trifluoroacetic acid in water and acetonitrile in the ratio 42:58 v/v) at a flow rate 1.0 ml/min was set and the developed analytical procedure became fast and simple. Chromatographic determination was performed on a Purospher® RP – 18 column at room temperature and a UV detector set at 230 nm. Results: The developed method was validated for linearity in the range 0.5–125 µg/ml for the bulk drug and 0.48–120 µg/ml for plasma. Calibration curves were linear over the selected ranges with correlation coefficients (R2) greater than 0.999. The coefficients of variation for intra- and inter-assay were <2% for both methods – bulk drug and plasma determination. Conclusion: The developed effective and specific method can be applied in routine clinical practice for drug therapy monitoring.
Keywords: Diflunisal; Bioanalysis; HPLC-UV; Validation